The irrelevance of R&D intensity in the ESG disclosure? Insights from top 10 listed companies on global Islamic indices - Muhammad Afi Ramadhan; Ratna Mulyany; Evi Mutia (Cogent Business & Management, 2023)
This study investigates the potential influence of several pertinent factors including R&D intensity, directors' education, and firm size towards ESG disclosure. This study utilised samples from top 10 companies listed in 6 (six) different Global Islamic Indices with a three-year observation period (2017-2019) resulting in 99 observations. Global Islamic listed companies have rarely been studied in ESG-related issues. The pre-COVID-19 pandemic period was chosen to avoid the potential effects of pandemic on the subject of this study. Multiple linear regression analysis was employed to test the hypotheses. It was found that all the independent variables simultaneously influence the ESG disclosure, while partially directors' education are influencing the variable, and both R&D intensity and firm size do not influence the ESG disclosure. Confirming the agency theory, it is argued that the board characteristics are important in predicting overall board performance in carrying out their monitoring responsibilities, in this case, monitoring and encouraging companies to disclose more ESG information in their sustainability reports. This study signifies the role of directors even within the Islamic listed companies that the more highly educated the members of the board, they will tend to disclose more ESG information on their sustainability reports. This study contributes to the existing ESG disclosure and sharia-based investing literature by utilizing global-based indices instead of local indices in Muslim-majority countries, mirroring the current uptrend in world-wide sharia investing and the call for companies to be more sustainable in doing their business.
Keywords: M41; 650; directors' education; environment; ESG disclosure; firm size; governance; Islamic index; R&D intensity; social responsibility; sustainability; sustainability reporting